27 Ergonomic risk factors in intensive care unit and musculoskeletal symptoms. (24th April 2018) - Dilek, Banu; Beyan, Ayse Coskun; Özcan, Sabriye; Demirel, Tugba; Işık, Özay; Demiral, Yucel
Abstract : Introduction: Musculoskeletal disorders (MSD) represent a significant occupational problem in intensive care unit (ICU) workers. This study aimed to determine ergonomic risk factors and the musculoskeletal symptoms in ICU workers in university hospital. Methods: Ergo team was created by the occupational health department in the hospital. The socio demographic data were obtained by a questionnaire. The clinical assessments were performed by a physiatrist. Cornell Musculoskeletal Discomfort Questionnaire was used for musculoskeletal symptoms assessment. Walk-through survey performed to determine main jobs and tasks in ICUs. The Rapid Entire Body Assessment (REBA) scale was used to assess the ergonomics risks for the nurses. Results: There were 30 patient' bed in both intensive care units. Twelve doctors(10.7%), sixty four nurses (62.7%) and twenty seven staff members (26.2%) worked in two ICUs included in the study. Each nurse was responsible for two patients while the doctors and staff members were responsible entire units. 102 workers of those 56 from internal medicine ICU (IMICU) (56%) and 46 from anaesthesia ICU (AICU) (46%) workers were participated to the study. 60.7% of the study group was female and the mean age was 32±6.4 in IMICU and 33.1+5.7 in AICU (p=0.3). According to the Cornell scale, 52 (50.9%) had neck pain, 58 (56.8%) had back pain and 25 (24.5%) had wrist pain. Two ergonomically high risk tasks (patient positioning and working with monitor) were identified. The nurses' mean REBA score was 9.7+1.6 in anaesthesia ICU and 8.7+2.0 in internal medicine ICU (p=0.8) for patient position taks. The mean REBA scores for anaesthesia ICU were 6.1+1.6 and 4.8+1.4 (p=0.7) respectively. Conclusion: More than half of ICU workers had neck, back and wrist pain. ICU nurses had high ergonomics risks. In these units, 'ergonomic risk prevention programmes' should be implemented by occupational health teams.